Canonical Literature and Paraliterature: impulses of allegorism and deconstructionism in writing detective stories - Naujokaitienė, Elina (Respectus Philologicus, 2006)
Minette Walters, the queen of British detective Stories, and Luca Di Fulvio, ltalian prose writer and the winner of European Detective, elegantly narrate mysteries of murders, find keys of intimate things and emphasise the genre of Folkner style. How can one effectively manage materials, maintain common sense, and get into the sphere of private offices? Using the characters of lawyers, judges and policemen, the European detective presents an obsessive idea of action for action, analyses social surroundings the space of prisons and establishes new neorealistic stylistics. Because of detective Intrigue, the Great European classical art gets a melancholic character and gives an effect of ensemble. Villainous portraits of ex-terrorists have a sense of metaphysical disappointment and are related to  the topic of the search for the Holy Grail. On the basis of confrontative and explicative literature theories (Certeau, Derrida), the article typologises a detective story and analyses its literary genesis from the Middle Ages to Postmodernism.
Keywords: virtual consciousness; black library; the balance of paradoxes